Peran Kinerja Guru Dalam Membentuk Karakter Kerjasama Pada Siswa Kelas IV - Devy Nur Pika Putri; Moch. Bahak Udin By Arifin (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
Teachers play an important role in learning, including in building the character of students in class. One of these character formations is the character of cooperation. The existence of a cooperative character will have a positive impact on student learning models in the classroom so that students can adjust when they are in a group discussion. This study aims to analyze the role and impact of teacher performance in shaping the character of cooperation applied at MI Muhammadiyah 1 Jombang. This study uses a qualitative method by collecting data by means of in-depth interviews, observation, documentation, and questionnaires. The subjects of this study were 29 students and teachers of related subjects. The results of this study are the teacher's role in forming the cooperative character of students at MI Muhammadiyah 1 Jombang, namely by applying for the teacher's role as a teacher, mentor, and educator during learning which is varied using the values ​​of cooperation including guidance, direction and helping students when discussing problems. This has a positive impact on students being more responsive and communicative. It can be seen from the table that the percentage of students at MI Muhammadiyah 1 Jombang is 80%, which shows a positive impact on behavior when learning in class with an awareness of the role in groups.